Hubungan Antara Maternal Fetal Attachment (MFA) Dengan Pola Kesehatan Kehamilan - Suryaningsih, Endang Koni; Purnamasari, Vita; Kusuma, Nur Intan; Iswati, Nining; Lesdianti, Kiki (Jurnal Ilmiah Kesehatan, 2025)
Health practices during pregnancy, such as smoking, consuming alcohol, or failing to meet nutritional requirements, can have serious impacts on the health of both the mother and fetus. These risks include premature labor, spontaneous abortion, anemia, and other dangerous complications. Additionally, insufficient ANC (Antenatal Care) visits can hinder the early detection of danger signs or pregnancy complications, such as anemia, preeclampsia, or maternal abnormalities, which could potentially endanger the birthing process. Maternal-fetal attachment (MFA) is an important factor that can significantly influence health practices, subsequently impacting the health and well-being of both pregnant women and their unborn fetuses. This study aimed to determine the relationship between maternal-fetal attachment and health practices during pregnancy at PMB Anisa Mauliddina. The research utilized quantitative descriptive analytical design with cross-sectional approach. The study was conducted at the Amanah Husada Clinic in Gunung Kidul Regency, involving 86 third-trimester pregnant women selected through purposive sampling. The results showed no significant relationship between maternal-fetal attachment and health practices during pregnancy at PMB Anisa Mauliddina, with a p-value of 0,084. In conclusion, this study found no correlation between maternal-fetal attachment and health practices during pregnancy at PMB Anisa Mauliddina.